Noi Metode De Predare Și Învățare Pentru Perioada Post-Pandemică - Raykova, Zhelyazka; Raganova, Janka; Stoyanova, Diana; Tsokov, Galin; Stoyanov, Stefan; Hruska, Martin; Spodnıakova Pfefferova, Miriam; Petrışor, Iulian; Bulıgıu, Ion; Constantin Sararu, Silviu; Marıus Etegan, Cristian; Yılmaz, Ece; et al. (Akademisyen Yayınevi Kitap DOI Portalı, 2023)
-